Changes in VEGFR1 and VEGFR2 expression and endothelial cell maturity in laboratory animals with a model of Alzheimer’s disease - M. V. Kukla; A. S. Averchuk; A. V. Stavrovskaya; N. A. Rozanova; A. K. Berdnikov; N. A. Kolotyeva; A. B. Salmina (Бюллетень сибирской медицины, 2025)
Aim. To evaluate the expression of VEGFR1 and VEGFR2 and the maturity of endothelial cells in neurogenic niches in the model of Alzheimer’s disease.Materials and methods. The study was carried out on 6-month-old male C57BL/6 mice. The experimental group (n = 15) received 2 µl of 1 mM Aβ25-35 solution in the CA1 hippocampal region, while the control group (n = 15) received normal saline. Brain plasticity was assessed at day 10, 17, and 38 after surgery by the passive avoidance test. The expression of VEGFR1, VEGFR2, and CLDN5 was assessed by immunohistochemistry and the Image ExFluorer imaging system.Results. In the control group, cognitive training stimulated angiogenesis in the neurogenic niches of the brain, which was accompanied by the formation of microvasculature with fully mature endothelium. In the experimental group, an early and pronounced increase in the VEGFR1 expression was observed by day 7 after cognitive training, which was followed by impaired barrier formation and high VEGFR2 expression by day 28 after cognitive training. These changes were associated with the formation of small vessels with structural incompetence of endothelial cells.Conclusion. Angiogenesis in neurogenic niches of the animals with the model of Alzheimer’s disease is characterized by incompetent mechanisms regulating the subpopulation composition of endothelial cells, impaired stabilization of the endothelial layer, and a decrease in the maturation rate of endothelial cells in newly formed microvessels by the time of cognitive deficit manifestation. This may contribute to microcirculatory dysfunction and impaired neurogenesis in neurogenic niches as well as to the development of pathological permeability and neuroinflammation. On the whole, the disruption of angiogenesis in neurogenic niches observed in the animal model of Alzheimer’s disease suggests a potential contribution of this mechanism to the development of aberrant brain plasticity.